(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Topology optimization is esoteric. Computer-aided design includes. Design objectives and feasibility are the goals. This study optimizes the crane hook, a common mechanical component with complex geometry, using topology. The crane hook should be light but strong. Photoelasticity allows experimental verification of the design’s stress distribution by visualizing and stress patterns in birefringent property materials. Formulating the topology problem, design space, objective function, and constraints starts the study. The initial design and photoelasticity optics iterations are simulated using finite element analysis. Density method Isotropic Material with Penalization algorithm optimizes by iteratively updating the density distribution to improve the objective function while satisfying constraints. The design is then prototyped using a Photoelastic birefringent material. A known load and boundary conditions under polariscope experimental set-up stress the crane hook prototype. Computational topology and finite element analysis stress distributions are compared to isochromatic fringe principal stress patterns (1–2). Experimental and simulated results validate the design’s stress, displacements, and reliability. The study showed 23.45% weight reduction while maintaining crane hook structural integrity. Photoelasticity experimentally verifies stress distribution, boosting confidence in the design. Computational simulations and photoelasticity allow mechanical component validation.